Using ecosystem service assessments to support participatory marine spatial planning. (15th April 2020) - Friedrich, Laura A.; Glegg, Gillian; Fletcher, Stephen; Dodds, Wendy; Philippe, Manuelle; Bailly, Denis
Abstract: With growing interest in ocean uses for sustainable economic development, there is an increasing need for cross-sectoral marine spatial planning to balance different resource uses and conservation requirements. Ecosystem service assessments can provide the evidence to inform marine spatial planning decisions. Existing case studies suggest that these assessments can also have positive effects on the engagement of marine stakeholders in management and planning processes. Stakeholder engagement is a central element in marine spatial planning and other area-based management approaches. However, in a marine context, engagement is often difficult due to the lack of clear boundaries in the ocean, traditionally sectoral marine management and limited understanding of marine ecosystems. The study presented here investigated ecosystem service assessments as a tool for improving marine stakeholder engagement. Stakeholder experiences with ecosystem service assessments in six marine management and planning case studies were analysed to identify why, how and under what conditions ecosystem service assessments can support effective engagement. The findings show that under the right conditions, ecosystem service assessments can provide an inclusive and integrative platform for engagement, enable a better understanding of marine ecosystems, human-ecosystem interactions and management contexts, and support better stakeholder relationships. Stakeholder participation also improves the evidence base for ecosystem service assessments. Thus, involving stakeholders in ecosystem service assessments can improve marine spatial planning decisions and lead to better management and conservation outcomes for the ocean. Highlights: Ecosystem service assessments enable inclusive marine stakeholder participation. They improve stakeholder dialogue and understanding of marine management contexts. This supports more effective stakeholder engagement in marine spatial planning. It contributes to better stakeholder relationships and more informed plans. A systems-based view and neutral perspective are key to this engagement potential.